Analysis of differentially expressed genes of Rhizoctonia solani during the sclertium formation - CHEN Xiao-yao; WANG Wei; WANG Zheng-yi; CHEN Wei-liang (浙江大学学报. 农业与生命科学版)
Subtractive cDNA library of differentially expressed genes during the sclertium formation of Rhizoctonia solani, GD-118 strain, was constructed by using suppression subtractive hybridization (SSH) technique combined with virtual Northern blot. The hypha mRNA was used as the driver and the sclertium mRNA was applied as the tester. Further PCR screening showed that the size of the inserts was mainly between 200 to 500 bp. The effectiveness of the subtractive hybridization was verified by virtual Northern blot of colonies randomly selected using hypha, sclertium cDNA sequence as probes. Finally, 28 specific sclertium formation-related gene fragments were obtained after sequencing and homology-blasting, which were mainly related to stress response, transcription regulation, signal transduction and metabolism in the pathogen. Results above provide scientific clues to understand the mechanism of the sclertium formation of R. solani.